2021
DOI: 10.15302/j-sscae-2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Paths for Carbon Peak and Carbon Neutrality in Transport Sector in China

Abstract: Peaking carbon dioxide emissions and achieving carbon neutrality is a major strategic decision taken by China and it brings significant pressure and challenges to the transport sector. Peaking carbon emissions is an important direction for the highquality development and green transformation of the transport sector. This study analyzes the status quo of green development and carbon emission in China's transport sector and identifies the challenges for achieving the carbon peak and carbon neutrality goals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…To achieve the green and low-carbon economic development target, the Chinese government encourages technological innovation and technology-dominated transportation reforms. Li et al [56] analyze green transportation development and carbon emissions and suggest some solutions, such as further optimizing transportation structures, improving the efficiency of transportation equipment, promoting the applications of lower-carbon equipment, and increasing transportation-organization efficiency. Huang et al [57] suggest that enhancing low-carbon technology promotions and encouraging technological innovation may help achieve the carbon-reduction target.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the green and low-carbon economic development target, the Chinese government encourages technological innovation and technology-dominated transportation reforms. Li et al [56] analyze green transportation development and carbon emissions and suggest some solutions, such as further optimizing transportation structures, improving the efficiency of transportation equipment, promoting the applications of lower-carbon equipment, and increasing transportation-organization efficiency. Huang et al [57] suggest that enhancing low-carbon technology promotions and encouraging technological innovation may help achieve the carbon-reduction target.…”
Section: Discussionmentioning
confidence: 99%
“…As the total amount of cargo transportation continues to increase, the pressure to reduce emissions at ports will be further aggravated. The question of how to realize energy saving, emission reduction, and the green transformation of ports has become the focus of social attention [1]. Maritime transportation contributes approximately three per cent of global carbon dioxide emissions annually.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that carbon emissions from China's road, waterway, and air transport sectors have increased, while rail transport carbon emissions have decreased (Li et al, 2019). More importantly, Li et al (2021a) found significant sectoral differences in China's transportation carbon emissions in 2019. The share of railroad carbon emissions in total transportation carbon emissions is only .68%, much lower than the shares of carbon emissions from roads (86.76%), waterways (6.47%), and aviation (6.09%).…”
Section: Introductionmentioning
confidence: 99%